KESEJAHTERAAN SUBJEKTIF (SUBJECTIVE WELL-BEING) DITINJAU DARI SOSIO-DEMOGRAFIS DI KALANGAN REMAJA YATIM YANG TINGGAL DI PANTI ASUHAN/PESANTREN YATIM - Ibda, Fatimah; Ishak, Noor Azniza binti; Mohd Nasir, Mohd Azrin bin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: Although there was a little interest in investigating the well-being issues of orphaned adolescents. This study is preliminary research of subjective well-being and socio-demographic correlation among orphanaged adolescents. The main aim of this study was to assessed the relationship between subjective well-being and socio-demographic (gender, length of stay orphanage, source of funds orphanage, education level of orphan, location and model of orphanage). Participants were a total 285 orphanage youth (age range of 11-20 years) from 5 orphanage in Banda Aceh and Aceh Besar District, Aceh Province, Indonesia. Data were collected using the Multidimensional Student Life Satisfaction Scale and socio-demographic profiles. The data were analyzed by using chi-square analysis. The results showed that, there was a significant correlation between subjective well-being and socio-demographic (gender and location of the orphanage). While subjective well-being and socio-demograhic (length of stay orphanage, source of fund orphanage, education level of orphan and orphanage model) was no significant correlation. Further research is needed to gain comprehensive understanding for subjective well-being of socio-demografic factors among orphanaged adolescents. Recommendations for further research in this context are discussed.Keywords: Subjective Well-Being; Socio-Demographic; Orphan Adolescents; Orphanages.Abstrak: Meskipun minat dalam penyelidikan isu kesejahteraan subjektif remaja yatim masih sangat sedikit, penelitian ini merupakan studi awal untuk menyelidiki kesejahteraan subjektif dan sosio-demografis di kalangan remaja yatim. Penelitian ini bertujuan menguji hubungan antara kesejahteraan subjektif dan sosio-demografis (jenis kelamin, lama tinggal, sumber dana, tingkat pendidikan, lokasi panti asuhan/pesantren yatim, dan model panti asuhan/pesantren yatim) remaja yatim yang tinggal di panti asuhan/pesantren yatim. Partisipan berjumlah 285 remaja yatim yang tinggal di panti asuhan/pesantren yatim (usia 11-20 tahun) dari 5 panti asuhan/pesantren yatim yang ada di Kota Banda Aceh dan Kabupaten Aceh Besar, Provinsi Aceh, Indonesia. Data dikumpulkan menggunakan Multidimensional Students’ Life Satisfaction Scale dan profil sosio-demografis. Analisis data menggunakan analisis chi-square. Hasil penelitian menunjukkan bahwa ditemukan hubungan yang signifikan antara kesejahteraan subjektif dan sosio-demografis (jenis kelamin dan lokasi panti asuhan/pesantren yatim). Sedang kesejahteraan subjektif dan sosio-demografis (lama tinggal, sumber dana, tingkat pendidikan, model panti asuhan/pesantren yatim) memiliki hubungan yang tidak signifikan. Penelitian lanjutan dibutuhkan untuk mendapatkan pemahaman lebih luas dan menyeluruh terkait domain spesifik sosio-demografis dari kesejahteraan subjektif remaja yatim. Rekomendasi untuk penelitian lanjutan dalam konteks ini didiskusikan.Kata Kunci: Kesejahteraan Subjektif; Sosio-Demografis; Remaja Yatim; Panti Asuhan/Pesantren Yatim.